Interdisciplinary teaching through outdoor education - Bunting, Camille J., ....- (Champaign, IL : Human Kinetics, 2006)
Interdisciplinary Teaching Through Outdoor Education provides teachers and recreation and outdoor leaders with outdoor activities as well as the expertise to expand students' understanding of the outdoors and develop their character. Units are included for challenge initiatives that don't require a ropes course, frontcountry camping, backcountry camping, outdoor cooking techniques, land navigation, casting and angling, and archery. Also discussed are rock climbing and canoeing and kayaking. Developed for teachers and leaders of children and youth aged 10 to 15, this book does the following: •Grounds readers in the principles of teaching outdoor education •Provides them with current practices •Details seven introductory, ready-to-implement units of outdoor adventure activities presented so that novices to a particular activity can teach that unit •Includes easy-to-teach, step-by-step experiential education lesson plans that focus on basic outdoor skills, with character development qualities linked to each lesson •Helps teachers meet NASPE and multidisciplinary national standards for students in grades 5 to 10 In addition to the units and lesson plans, Interdisciplinary Teaching Through Outdoor Education provides teachers and leaders with the following: •Interdisciplinary connections in each lesson •Strategies for questioning students so that they find the answers and for developing character qualities within each lesson •Preparation, teaching, and assessment techniques for each lesson •Safety and teaching tips for each activity And because planning time is a rare commodity for teachers, the author has gone to great lengths to provide the background and help that teachers need in order to give outdoor education a try. In fact, through Interdisciplinary Teaching Through Outdoor Education, teachers and leaders have the tools and guidance to develop their own outdoor programs.
Part I introduces readers to outdoor education and its role in school. It explores the foundations and methods for using outdoor education and highlights its interdisciplinary connections. Part II provides detailed instructions for the novice in conducting outdoor education lessons as well as unit plans for seven outdoor education areas with sample lesson plans and activities. Part III delves into school programming, including planning field trips and starting a school-based outdoor education program. Outdoor education has grown to be a multidisciplinary concept. This book captures the depth and breadth of that concept, provides outdoor adventure activities, and details the vital components of fostering learning and character development through outdoor education. Interdisciplinary Teaching Through Outdoor Education will more than meet teachers' and leaders' needs in using the outdoors to educate children and youth aged 10 to 15.
Includes bibliographical references (p. 239-241).
Keywords: Buitenactiviteiten; Didactiek; Interdisciplinary approach in education; Outdoor education